PELATIHAN PUBLIC SPEAKING UNTUK MENUNJANG KEMAMPUAN PRESENTASI BAGI SISWA SMAN 1 MARGAHAYU KABUPATEN BANDUNG - Charisma Asri Fitrananda; Rini Anisyahrini; Mochamad Iqbal (LPPM UPN Veteran Jakarta, 2018)
Abstract Ability in public speaking is an important part in every activity, especially activities in the academic environment. In reality, there are still few school students who have the public speaking skill. Departing from this, the Community Service Team of the Department of Communication of the University of Pasundan took the initiative to conduct services on Public Speaking Training. Dedication was carried out at SMAN 1 Margahayu Bandung Regency, the selection of these locations was inseparable from the many potential students who wanted to have the ability of public speaking to speak in public and presentation techniques, but had not been fully honed. The method used in this training is giving material, discussion and simulation. In training activities carried out, exploring the potential of students is done by asking them to speak in public without preparation. This is indicated by their ability to practice knowledge while taking public speaking training. The training which ended with the simulation showed that there was a good potential for students of SMAN 1 Margahayu Bandung Regency in the field of public speaking. Potential will just evaporate if it is not sharpened continuously to face the world of lectures and jobs in the future.